2006
DOI: 10.1152/ajpendo.00374.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced metabolic effects in human adipocytes are independent of endogenous nitric oxide

Abstract: ller. Cytokine-induced metabolic effects in human adipocytes are independent of endogenous nitric oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(76 reference statements)
0
6
1
Order By: Relevance
“…In contrast, in cultured human adipocytes, iNOS mRNA was activated only in a transient manner in response to inflammatory cytokines, but the protein was undetectable (although readily observable in 3T3-L1 adipocytes) (262). Consistently, iNOS inhibitors could not prevent the decrease in insulinstimulated glucose uptake that was induced by exposure to inflammatory agents (262). Regardless of this discrepancy between the two cell types, it appears based on in vitro experimental systems that inhibiting either mitochondrial or NADPH-derived ROS generation, and at least in muscle cells also iNOS-induced NO generation, can relieve insulin resistance.…”
Section: Preventing Ros/rns Generationmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, in cultured human adipocytes, iNOS mRNA was activated only in a transient manner in response to inflammatory cytokines, but the protein was undetectable (although readily observable in 3T3-L1 adipocytes) (262). Consistently, iNOS inhibitors could not prevent the decrease in insulinstimulated glucose uptake that was induced by exposure to inflammatory agents (262). Regardless of this discrepancy between the two cell types, it appears based on in vitro experimental systems that inhibiting either mitochondrial or NADPH-derived ROS generation, and at least in muscle cells also iNOS-induced NO generation, can relieve insulin resistance.…”
Section: Preventing Ros/rns Generationmentioning
confidence: 87%
“…Metformin and troglitazone prevented these effects through their capacity to activate AMPK (both an activator of AMPK and a pharmacological inhibitor of iNOS prevented inflammation-induced insulin resistance) (337). In contrast, in cultured human adipocytes, iNOS mRNA was activated only in a transient manner in response to inflammatory cytokines, but the protein was undetectable (although readily observable in 3T3-L1 adipocytes) (262). Consistently, iNOS inhibitors could not prevent the decrease in insulinstimulated glucose uptake that was induced by exposure to inflammatory agents (262).…”
Section: Preventing Ros/rns Generationmentioning
confidence: 99%
“…IFN-c co-administration inhibited IL-1b-mediated PCT and CGRP secretion by 78 and 34%, respectively, but augmented IL-1b-mediated adrenomedullin secretion by 50% [4]. CALC-I and -II mRNAs were induced by exogenous CGRP and adrenomedullin, suggesting a positive autocrine feedback loop within the expression of the CT peptide superfamily [3][4][5]27]. Preliminary experimental evidence also suggests that this feedback loop is markedly enhanced by incubation with cycloheximide, an unspecific inhibitor of protein synthesis.…”
Section: Calcitonin Peptides Are Prototypes Of Hormokinesmentioning
confidence: 94%
“…However, at the highest concentration utilised (5 mg?L -1 ), PCT did not inhibit NO production and had no effect on unstimulated cells. Recent findings suggest a less prominent role of NO in human physiology and metabolism, as compared with rodents [27,130].…”
Section: The Central Role Of Hormokines In Host Defencementioning
confidence: 99%
“…This calcium- and inflammation-regulated peptide appears to have important immunomodulatory actions by 1) tempering inflammation through NFkB inhibition and 2) increasing endothelial production of PGI 2 , a prostaglandin with anti-inflammatory activities [61]. Interestingly, CGRP is expressed in rodent and human white adipose tissue (WAT), where Linscheid et al showed it can be induced by pro-inflammatory insults (e.g., [66, 67]). The peptide is also a powerful vasodilator, and CGRP has been proposed to contribute to the beneficial effects of dietary calcium/dairy in thwarting hypertension [68, 69].…”
Section: Dairy and Cardiometabolic Health: Potential Mechanismsmentioning
confidence: 99%